Relationship between adherence to hepatitis C virus therapy and virologic outcomes: a cohort study - Re, Vincent Lo (2011)
BACKGROUND: Adherence to hepatitis C virus (HCV) therapy with pegylated interferon and ribavirin has been incompletely examined. OBJECTIVES: To evaluate the relationship between adherence to HCV therapy and early and sustained virologic response, assess changes in adherence over time, and examine risk factors for non-adherence. DESIGN: Retrospective cohort study. SETTING: National Veterans Affairs Hepatitis C Clinical Case Registry PATIENTS: 5,706 HCV-infected patients (genotypes 1, 2, 3, or 4) with at least one prescription for pegylated interferon and ribavirin between 2003 and 2006 and HCV RNA results prior to and after treatment initiation. MEASUREMENTS: Adherence was calculated over 12-week intervals using pharmacy refill data. Endpoints included early virologic response (decrease of ≥2 log(10) HCV RNA at 12 weeks) and sustained virologic response (undetectable HCV RNA 24 weeks after end of treatment). RESULTS: Early virologic response increased with higher levels of ribavirin adherence over the initial 12 weeks of therapy (genotype 1, 4: 25/68 [37%] with the lowest category [≤40% adherence] versus 1,367/2,187 [63%] with the highest category [91–100% adherence], p<0.001; genotype 2, 3: 12/18 [67%] with ≤40% adherence versus 651/713 [91%] with 91–100% adherence, p<0.001). Among genotype 1 and 4 patients, sustained response increased with higher ribavirin adherence over the second, third, and fourth 12-week intervals. Results were similar for interferon adherence. Mean adherence to interferon and ribavirin decreased 3.4% and 6.6% per 12-week interval, respectively (test for trend, p<0.001 for each drug). Patients prescribed growth factors or thyroid medications during treatment had higher mean antiviral adherence. LIMITATIONS: Observational study without standardized timing for outcomes measurements. CONCLUSIONS: Early and sustained virologic responses increased with higher levels of adherence to interferon and ribavirin. Adherence to both antivirals declined over time, but more so for ribavirin.